MANAJEMEN PEMBINAAN KEDISIPLINAN SISWA: STUDI KASUS PADA ABSENSI FINGERPRINT BERBASIS SMS GATEWAY DI SMK NU KAPLONGAN INDRAMAYU - Ade Apriyanto (Gema Wiralodra, 2019)
The purposes of this research are to know the management of students’ discipline development trough fingerprint attendance system based on SMS gateway in SMK NU Kaplongan, and to determine the effectiveness of the students’ discipline development management through fingerprint attendance system based on SMS gateway SMK NU Kaplongan, and to determine the implications of the students’ discipline development through fingerprint attendance based on SMS gateway about increasing students discipline in SMK NU Kaplongan. The method of research which is used is a qualitative method. The techniques of accumulation data are observation participant, in-depth interviews, documentation, and triangulation. The results of this research are firstly the discipline of student can be materialized trough applying the rules. Applying fingerprint attendance system through some steps, they are fingerprint identification and matched with student ID numbers and also their parent phone numbers. The students do it, and the data will be sent to the school computer, it will be processed and sent to the central server. Finally, the data will be sent to the head master, teachers, and their parents.